Avaliação do desempenho dos acessos vasculares no serviço de diálise do Hospital São Lucas da PUCRS - Paula, Mariane Amado de (2022)
Introduction: Quality of life and life span in patients with chronic kidney disease on dialysis depends on the maintenance of a patent and functional vascular access with a low rate of complications. Autogenous fistula has the best access performance compared with other dialysis accesses, especially the radiocephalic fistula in non-dominant forearm, which is the first choice when feasible. The use of central venous catheter for dialysis access has a negative impact on the performance of an arteriovenous fistula and is associated with inflammation. Objective: The aim of this study is to evaluate the performance of vascular accesses in patients on a chronic hemodialysis program at the Renal Unit of Hospital São Lucas da PUCRS. Secondary aims are to classify vascular access according to their patency, infection rate, and inflammatory status. Method: Observational, cross-sectional and descriptive study with 91 patients in a chronic dialysis program, with 59 patients (65%) in the arteriovenous fistula (AVF) group and 32 patients (35%) in the central venous cateter (CVC) group. Results: The adequacy rate was 67% in total sample; in the analysis by subtypes, arteriovenous fistula adequacy rate was 67.8% and catheter was 65.6%. The causes of fistula inadequacy, associate with the highest prevalence ratio, were non-mature AVF (PR: 4,055; 95% CI: 2,017-8,151), pseudoaneurysm (PR: 6,580; 95% CI: 3,723-11,629) and hematoma (PR: 4,360; 95% CI: 2,125-8,946), all with P < 0.001. In the catheter group, the causes of inadequacy with the highest prevalence ratio were access thrombosis, indicating use of thrombolytics, (PR: 11,103; 95% CI: 4,746-25,977; P < 0.001) and catheter infection (PR: 2,984; 95% CI : 1,293-6,889; P = 0.010). Primary AVF patency median was 72 months and CVC patency median was 7 months (P < 0.001). There was no statistically significant difference between the values of serum inflammatory markers in relation to the adequacy or inadequacy of access, in the two groups studied. Conclusions: The adequacy rates of vascular accesses did not differ between two groups although the primary and functional patency of arteriovenous fistulas is higher than catheters. Infection in dialysis catheters is associated with worse access performance. We did not find association between increased systemic inflammatory activity and access performance.